2018
DOI: 10.1111/jftr.12291
|View full text |Cite
|
Sign up to set email alerts
|

Half‐Sibling and Stepsibling Relationships: A Systematic Integrative Review

Abstract: Increases in divorce, remarriage, and stepfamily formation have added complexity to sibling composition. Biological siblings have been found to be key players in children's lives, and relationships with half and stepsiblings also likely influence individual development and adjustment. In this systematic integrative review, we synthesize and critique 46 studies on half and stepsibling relationships, a literature that has seen marked growth in recent years. Researchers have focused predominately on two areas: in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 59 publications
3
61
0
Order By: Relevance
“…How do adult siblings navigate care of an older stepparent? An established body of scholarship has examined stepfamilies earlier in the life course (Ganong & Coleman, 2018; Sanner, Russell, Coleman, & Ganong, 2018); however, less attention has been directed toward understanding stepfamily formation and maintenance among later‐life families.…”
Section: Review Of Current Knowledge On Sibling Relationships In Adulmentioning
confidence: 99%
“…How do adult siblings navigate care of an older stepparent? An established body of scholarship has examined stepfamilies earlier in the life course (Ganong & Coleman, 2018; Sanner, Russell, Coleman, & Ganong, 2018); however, less attention has been directed toward understanding stepfamily formation and maintenance among later‐life families.…”
Section: Review Of Current Knowledge On Sibling Relationships In Adulmentioning
confidence: 99%
“…Although less is known about half-sibling relationships compared with full-sibling relationships, research on this topic is growing. In a systematic integrative review of research on half-and stepsiblings, Sanner, Russell, Coleman, and Ganong (2018) found that the research suggests small but consistent deficits associated with the presence of half-siblings in the household-lower parental involvement, educational achievement, and economic well-being (Brown, Manning, & Stykes, 2015;Ginther & Pollak, 2004;Halpern-Meekin & Tach, 2008;Strow & Strow, 2008;Turunen, 2014); more antisocial behavior, depressive symptoms, and parent-child conflict (Apel & Kaukinen, 2008;Fomby, Goode, & Mollborn, 2016;Halpern-Meekin & Tach, 2008;Harcourt et al, 2015;Schlomer, Ellis, & Garber, 2010;Strow & Strow, 2008); increased risk of family dissolution (Jensen & Clausen, 2003); early exit from the parental home (Aquilino, 1991); and more frequent unintentional childhood injuries (Tanskanen, Danielsbacka, & Rotkirch, 2015).…”
Section: Half-sibling Relationshipsmentioning
confidence: 99%
“…Whereas biological siblings may promote a sense of continuity and shared experience during family reorganization [20], the introduction of half- and stepsiblings may make it harder to define belongingness to the family after the divorce [21]. Studies focusing on siblings tend to find small but rather consistent negative effects of living with half- or stepsiblings on outcomes such as depressive symptoms and physical well-being, although youth may also report such relationships as a resource following parental divorce [22].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of family complexity may, however, be gender-dependent. Girls have been found to report worse relationships with stepsiblings than boys [22], and a recent study found higher levels of internalizing problems among girls but not among boys living with nonbiological siblings [25]. Few studies have, however, examined such gender-specific effects.…”
Section: Introductionmentioning
confidence: 99%